The role played by representatives of the Faculty of Law of Kazan University in statehood of the Republic of Tatarstan - L.T. Bakulina; D.Kh. Valeev (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, the contribution of the Faculty of Law of Kazan University to the development of the TASSR statehood was studied. Three major groups of events and persons were singled out based on the degree of their influence: lecturers and researchers, who worked at the Faculty of Law in different years (Faculty of Social Sciences, Law Institute); state and public figures; law enforcement and court officers. The transformation of the Faculty of Law in line with the reforms in the higher education system of the USSR was considered. Special attention was paid to the role of the Faculty of Law in the development of cities and infrastructure of the TASSR, as well as in ensuring the rule of law during the administration of justice. Through the prism of outstanding personalities of the Faculty of Law, the history of Tatarstan during the Soviet period was constructed.